Spontaneous detachment of the spiral overtube from the endoscope in the upper esophagus: a case report and literature review of a rare complication during motorized spiral enteroscopy - Wiedbrauck, Damian; Wiedbrauck, Felix; Freund, Ulrich; Rodenberg, Frauke; Prenzel, Jens; Hollerbach, Stephan (Zeitschrift für Gastroenterologie, 2023)
Background Motorized spiral enteroscopy (MSE) is a recent modality for diagnostic and therapeutic examination of the small bowel using a spiral-shaped overtube with an integrated electric motor attached to an endoscope. With growing evidence of its efficacy, MSE is increasingly being used by endoscopic facilities. We herein present an uncommon case of the detachment of the spiral overtube from the endoscope during MSE.Case Report We performed antegrade MSE in a 75-year-old female under general anesthesia for coagulation of multiple small-bowel arteriovenous malformations and resection of a polyp detected on a previous capsule endoscopy. The management was successful, and we had no passage difficulties. However, during the withdrawal phase of the enteroscope, the entire spiral overtube disconnected from the endoscopic shaft and became stuck in the esophagus and pharynx. Attempts to remove the lodged spiral using various endoscopic forceps, graspers, snares, or a dilatation balloon failed. Also, the laryngoscopic use of Magill forceps did not allow grabbing the spiral properly. Eventually, the spiral could be retrieved laryngoscopically with arthroscopic grasping forceps. This incident caused laryngeal swelling and bleeding lacerations of the upper esophagus, which were clipped on a subsequent gastroscopy. No further long-lasting complications occurred in the patient.Conclusion Detachment of the spiral from the enteroscope is a potentially life-threatening and challenging complication of MSE. Artificial ventilation under observation by an anesthesiologist allowed for calm management of this dangerous situation and increased the overall safety of the procedure. Hence, we believe that in the context of antegrade MSE, general anesthesia with endotracheal intubation should be mandatory.
Keywords: Antegrade motorized spiral enteroscopy; Enteroscopy; Spiral detachment; Endoscopy complication; General anesthesia; Endotracheal intubation; Polyp